Antimicrobial Resistance Determinants Circulating among Thermophilic Campylobacter Isolates Recovered from Broilers in Ireland Over a One-Year Period - Caoimhe T. Lynch; Helen Lynch; Sarah Burke; Kayleigh Hawkins; Colin Buttimer; Conor Mc Carthy; John Egan; Paul Whyte; Declan Bolton; Aidan Coffey; Brigid Lucey (MDPI AG, 2020)
Campylobacteriosis is the leading cause of human bacterial gastroenteritis, very often associated with poultry consumption. Thermophilic Campylobacter (Campylobacter jejuni and Campylobacter coli) isolates (n = 158) recovered from broiler neck skin and caecal contents in Ireland over a one-year period, resistant to at least one of three clinically relevant antimicrobial classes, were screened for resistance determinants. All ciprofloxacin-resistant isolates (n = 99) harboured the C257T nucleotide mutation (conferring the Thr-86-Ile substitution) in conjunction with other synonymous and nonsynonymous mutations, which may have epidemiological value. The A2075G nucleotide mutation and amino acid substitutions in L4 and L22 were detected in all erythromycin-resistant isolates (n = 5). The tetO gene was detected in 100% (n = 119) of tetracycline-resistant isolates and three of which were found to harbour the mosaic tetracycline resistance gene tetO/32/O. Two streptomycin-resistant C. jejuni isolates (isolated from the same flock) harboured ant(6)-Ib, located in a multidrug resistance genomic island, containing aminoglycoside, streptothricin (satA) and tetracycline resistance genes (truncated tetO and mosaic tetO/32/O). The ant(6)-Ie gene was identified in two streptomycin-resistant C. coli isolates. This study highlights the widespread acquisition of antimicrobial resistance determinants among chicken-associated Campylobacter isolates, through horizontal gene transfer or clonal expansion of resistant lineages. The stability of such resistance determinants is compounded by the fluidity of mobile genetic element.